Analysis of Environmental Risk Factors on the Leptospirosis Disease in Klaten, Central Java, Indonesia - Patria Sari Dewi; Setyo Sri Rahardjo; Bhisma Murti (Journal of Epidemiology and Public Health, 2020)
Background: The number of cases and mortality rates of Leptospirosis incidences in Klaten Regency is increasing from year to year. The study aims to analyze the environmental risk factors toward Leptospirosis incidences in Klaten Regency, Central Java, Indonesia.Subjects and Method: This was a case-control study conducted in Klaten Regency, Central Java. The study sample was all Lepto